Wolfram syndrome: A case report (Research, Society and Development, 2021)
Wolfram Syndrome is an autosomal recessive disease linked to the short arm of chromosome 4. The main clinical features are diabetes mellitus and optic nerve atrophy, as well as central diabetes insipidus, ataxia, sensorineural deafness and changes in the urinary tract. Other symptoms may be present, but less common. The harms in the life of its carriers are profound, due to the degenerative and non-remissive nature of the syndrome. The present study aims to report the case of a female patient, 23 years old (2020), born in Alfenas - Minas Gerais - Brazil, with the Wolfram Syndrome, as well disclose more knowledge about the syndrome. In addition, we address the need for interaction between different health professionals to minimize the suffering experienced by people with the disease and their families.